1986
DOI: 10.1111/j.1748-1716.1986.tb08002.x
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular pressure, EMG and blood flow during low‐level prolonged static contraction in man

Abstract: Seven men performed one-legged isometric knee-extension at 5% MVC for 1 h. Intramuscular pressure increased with contraction from its resting value of 14 (2-31) mmHg. Some intramuscular pressure recordings stayed at an almost constant level through the 1 h contraction, but most recordings showed large fluctuations from resting values up to 90 mmHg. The overall mean intramuscular pressure was twice the resting value. In some cases, EMG recordings confirmed that the changes in intramuscular pressure were related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
2
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(146 citation statements)
references
References 13 publications
(11 reference statements)
7
135
2
2
Order By: Relevance
“…The remaining 549 participants were randomly allocated to three intervention groups. A sample size of approximately 180 participants per intervention (allowing for a 10% loss to follow-up) was needed for 80% power to detect a 10% change in muscle strength (20). With a 10% change in muscle strength, there was a high likelihood that there would be a detectable impact on musculoskeletal symptoms in the neck and shoulder area.…”
Section: Study Populationmentioning
confidence: 99%
“…The remaining 549 participants were randomly allocated to three intervention groups. A sample size of approximately 180 participants per intervention (allowing for a 10% loss to follow-up) was needed for 80% power to detect a 10% change in muscle strength (20). With a 10% change in muscle strength, there was a high likelihood that there would be a detectable impact on musculoskeletal symptoms in the neck and shoulder area.…”
Section: Study Populationmentioning
confidence: 99%
“…This could mean that some motor units are active even at these low metabolic rates, which could result in them fatiguing prematurely (VØllestad, 1997). While the landmark study by Rohmert (1960) concluded that fatigue would not be induced with muscle exertions of less than 15% of maximum force, findings by Sjøgaard et al (1986) indicated this threshold force to only be 5% of maximum.…”
Section: Force Levelmentioning
confidence: 79%
“…RPE, a good indicator of perceptual fatigue (Iridiastadi & Nussbaum, 2006;Enoka & Duchateau, 2008), significantly increased, while maximal voluntary force production significantly decreased over time, which is also indicative of localized muscle fatigue (LMF) (Bigland-Ritchie & Woods, 1984;Garland et al, 1994;Enoka & Duchateau, 2008). The increase in EMG amplitude is often used to estimate muscle fatigue under sub-maximal isometric conditions since it infers an increased recruitment of motor units as a result of LMF (SjØgaard et al, 1986;Hermans & Spaepen, 1997;Hunter & Enoka, 2003;Chang et al, 2016). In the current study, EMG(RMS) only increased significantly for the 10-40%max force conditions, while the 0-50%max force conditions remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations